2013
DOI: 10.1308/003588413x13511609958217
|View full text |Cite
|
Sign up to set email alerts
|

Novel xylan-controlled delivery of therapeutic proteins to inflamed colon by the human anaerobic commensal bacterium

Abstract: INTRODUCTION Growth factors such as keratinocyte growth factor-2 (KGF-2) and transforming growth factor-beta (TGF-β) are important immunoregulatory and epithelial growth factors. They are also potential therapeutic proteins for inflammatory bowel disease. However, owing to protein instability in the upper gastrointestinal tract, it is difficult to achieve therapeutic levels of these proteins in the injured colon when given orally. Furthermore, the short half-life necessitates repeated dosage with large amounts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The full texts of the remaining 956 papers were further screened, and 910 articles were excluded; the reasons for this are shown in Figure 1 . Finally, 45 preclinical studies [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ] and 1 clinical study [ 61 ] fulfilled the inclusion criteria for this systematic review.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The full texts of the remaining 956 papers were further screened, and 910 articles were excluded; the reasons for this are shown in Figure 1 . Finally, 45 preclinical studies [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ] and 1 clinical study [ 61 ] fulfilled the inclusion criteria for this systematic review.…”
Section: Resultsmentioning
confidence: 99%
“…Growth factors play a key role in intestinal growth, regeneration, damage repair, and immunoregulation; however, it is difficult to achieve therapeutic functions with oral administration owing to their instability in the upper GIT. A study by Hamady et al [ 23 ] explored the gm probiotics producing keratinocyte growth factor-2 (KGF-2) or transforming growth factor-beta (TGF-β), which showed a significant prophylactic effect on limiting the development of intestinal inflammation in comparison to wild-type probiotics. Additionally, oral administration of recombinant L. lactis expressing insulin-like growth factor I (IGF-I) improved intestinal damage and barrier integrity and reduced colonic MPO activity in DSS-induced colitis mice; however, when compared with wild-type probiotics, it only achieved better alleviation of the histological damage score [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…L. lactis secreting interleukin-27 (IL-27) (Hanson et al 2014), anti-TNF (tumor necrosis factor) (Vandenbroucke et al 2010), and a serine protease inhibitor, Elafin, have been shown to prevent or reduce colitis in murine models. Furthermore, a Bacteroides ovatus strain engineered to produce human keratinocyte growth factor-2 (KGF-2) or transforming growth factor beta (TGF-β1) in response to xylan has also been shown to prevent dextran sodium sulfateinduced colitis in murine models (Hamady 2013). Additionally, immunomodulatory probiotic strains bioengineered to produce catalase or superoxidase dismutase demonstrated increased antiinflammatory properties compared to their wild-type variants (Carmen et al 2014).…”
Section: Immunomodulationmentioning
confidence: 99%
“…Administration of bacteria producing NAE precursors (NAPEs) to a polygenic mouse model of obesity successfully inhibited weight gain, as mice fed NAPE-producing E. coli exhibit a decreased food intake and increased metabolic rate [27]. Elsewhere, commensal species expressing anti-inflammatory compounds such as IL-10 [25], TGF-β1 [79], KGF-2 [80,81], serine protease inhibitors [82] and elafin [83] have been used to treat mouse models of induced colitis (Table 1), and trefoil factor-1 secreting L. lactis can ameliorate the inflammatory effects of chemotherapy and radiation therapy, although studies in this case focused on oral mucositis [84]. As a treatment for IBD, IL-10 L. lactis has even reached phase I clinical trials [28].…”
Section: Synthetic Probiotic Species – Engineered For Delivery Of Tmentioning
confidence: 99%